PENGARUH KUALITAS PELAYANAN, SANKSI PERPAJAKAN DAN BIAYA KEPATUHAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA PEMATANG SIANTAR - Silaban, Ketrin Olivia; Fitriyah , Fitriyah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the influence of service quality, tax sanctions, and taxpayer compliance costs together on taxpayer compliance. This research is a type of quantitative research. The sample in this study is individual taxpayers who are registered and classified as effective at KPP Pratama Pematang Siantar which totals 100 respondents. The results of the study show that the Quality of Tax Services on Taxpayer Compliance shows a tcount value (2.886) and a sig value (0.005) < 0.05, so it can be concluded that Service Quality has a positive and significant effect on the Compliance of Individual Taxpayers. if the variable of Tax Sanctions on Taxpayer Compliance shows a tcal value (4.691) and a value of sig (0.000) < 0.05, so it can be concluded that the variable of Tax Sanctions has a positive and significant effect on the Compliance of Individual Taxpayers. The variable Tax Compliance Cost to Taxpayer Compliance shows a tcal value (2.146) and a sig value (0.034) < 0.05, so it can be concluded that the compliance cost variable has a positive and significant effect on the compliance of individual taxpayers. Together, the variables of service quality, tax sanctions and taxpayer compliance costs affect the compliance of individual taxpayers, this can be seen that the significance value is 0.000. The significance probability value is less than 0.05.